Terrorism and cabinet duration: An empirical analysis - Martin Gassebner; Richard Jong-A-Pin; Jochen O. Mierau (ETH Zurich, KOF Swiss Economic Institute, 2007)
We examine the relationship between terrorism and cabinet duration. Our data set includes more than 2,400 cabinets in over 150 countries in the period 1968-2002. We find a small, but significant effect of terrorism on the probability of government failure. Furthermore, we find that the impact of terrorism depends on the type of attack and is larger in case of more severe attacks. Marginal effect calculations show that the impact of terror on cabinet duration is larger than the impact of economic variables such as economic growth, but less than the impact of a civil war or a government crisis. Our results suggest that cabinets in countries with high levels of terrorism are particularly vulnerable to terrorist attacks.
Keywords: D72; F59; C25; 330; terror; political stability; cabinet dissolution; Politische Gewalt; Dauer; Regierungswechsel; Welt